2013
DOI: 10.1080/00224545.2012.723642
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Social Exclusion at Work With Self-Defeating Behavior and Turnover

Abstract: Although studies indicate that perceived social exclusion is positively related to self-defeating behavior (SDB) and turnover intentions, studies have not integrated this research to examine the potential links among perceived social exclusion at work, SDB, and actual turnover. Using multisource data obtained from 246 employees and their immediate supervisors, we obtained support for a theoretical model in which perceived social exclusion relates directly and positively to turnover intentions and turnover, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 51 publications
1
36
0
1
Order By: Relevance
“…Finally, we contribute to the workplace ostracism literature by investigating its antecedents (Robinson et al., ). To date, the majority of workplace ostracism research has focused on the effects of being ostracized (e.g., Ferris, Lian, Brown, & Morrison, ; O'Reilly et al., ), such that the victim experiences psychological distress (Wu, Yim, Kwan, & Zhang, ), increased turnover (Renn, Allen, & Huning, ), and lower performance and reductions in commitment (Ferris et al., ). More recent research has started to investigate factors that lead to workplace ostracism (e.g., Scott et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we contribute to the workplace ostracism literature by investigating its antecedents (Robinson et al., ). To date, the majority of workplace ostracism research has focused on the effects of being ostracized (e.g., Ferris, Lian, Brown, & Morrison, ; O'Reilly et al., ), such that the victim experiences psychological distress (Wu, Yim, Kwan, & Zhang, ), increased turnover (Renn, Allen, & Huning, ), and lower performance and reductions in commitment (Ferris et al., ). More recent research has started to investigate factors that lead to workplace ostracism (e.g., Scott et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Ferris et al (2008) created a measure of employees' experiences with ostracism in the workplace and found that in addition to predicting threats to basic psychological needs, chronic experiences with ostracism also predicted negative job-relevant outcomes. Researchers found that ostracized employees felt dissatisfaction towards their job, showed decrements in performance, experienced emotional exhaustion and depression, and also exhibited more job withdrawal-tendencies (Ferris et al, 2008;Hitlan, Cliffton, & DeSoto, 2006;O'Reilly & Robinson, 2009;Leung, Wu, Chen & Young, 2011;Renn, Allen, & Huning, 2013;Scott, Tams, Schippers, & Lee, 2015;Wu, Wei, & Hui, 2011;Wu, Yim, Kwan, & Zhang, 2012). Researchers also found that workplace ostracism facilitated increases in counter-productive work behaviours and other antisocial tendencies (Gkorezis, Kalampouka, & Petridou, 2013;Hitlan & Noel, 2009;Thau, Aquino, & Poortvliet, 2007;Yan, Zhou, Long, & Ji, 2014;Zhao, Peng, & Sheard, 2013; but see examples of prosocial behaviors in Balliet & Ferris, 2013;Ferris, Lian, Brown, & Morrison, 2015;Xu, Huang, & Robinson, 2015).…”
Section: Social Ostracismmentioning
confidence: 99%
“…Racioethnically driven social exclusion at work, the “exclusion of the target [individual] from work‐related or social interactions as a result of his or her race or ethnicity” (Schneider, Hitlan, & Radhakrishnan, , p. 3), is the opposite of receptivity to outsiders. Being the target of ostracizing behavior at work puts the concerned individual under severe stress and, as a consequence, leads to emotional detachment from work, decreased job satisfaction, increased turnover (e.g., Renn et al, ), and even more severe, psychosomatic conditions such as social anxiety or depression (e.g., Antecol & Cobb‐Clark, ; Bell, Berry, Marquardt, & Galvin Green, ; Crocker & Lawrence, ; King, Dawson, Kravitz, & Gulick, ). Social exclusion of expatriates by locals is strongly associated with social identification processes (Tajfel & Turner, ) that hinge upon individuals’ salient racioethnic features.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Being the target of ostracizing behavior at work puts the concerned individual under severe stress and, as a consequence, leads to emotional detachment from work, decreased job satisfaction, increased turnover (e.g., Renn et al, 2013), and even more severe, psychosomatic conditions such as social anxiety or depression (e.g., Antecol & Cobb-Clark, 2008;Bell, Berry, Marquardt, & Galvin Green, 2013;Crocker & Lawrence, 1999;King, Dawson, Kravitz, & Gulick, 2012).…”
Section: Workplace Social Exclusion Cultural Skills and Job Satismentioning
confidence: 99%
See 1 more Smart Citation